Are “extreme consumption games” drinking games? Sometimes it's a matter of perspective - Zamboanga, Byron L. (2013)
Drinking games are widespread on college campuses and pose health risks to their players. Although there has been considerable research progress in the college drinking games literature, there does not appear to be a standard definition of the term “drinking games.” Researchers, however, have attempted to classify and categorize drinking games in a systematic manner. For example, one category of drinking games (e.g., chugging, keg stands) is often referred to as consumption or extreme consumption games. Questions remain as to whether or how these types of games align with researchers' definitions of drinking games or the categorization systems advanced by researchers in the field. Potential challenges regarding the definition and categorization of drinking games, particularly with respect to extreme consumption types of games, are discussed.